1) x2 + 6xy + 5y2 - 5y -x
= (x2 - x) + (5y2 - 5y) + 6xy
= x( x - 1) + 5y(y - 1) + 6xy
Mình làm được nhiêu đó thôi ! Bạn xem có đúng ko nha !
1)\(x^2+6xy+5y^2-5y-x\)
\(=x^2+xy-x+5xy+5y^2-5y\)
\(=x\left(x+y-1\right)+5y\left(x+y-1\right)\)
\(=\left(x+y-1\right)\left(x+5y\right)\)
x2 +6xy + 5y2 -5y - x
= x2 +xy + 5xy + 5y2 -5y - x
= (x2 +xy - x) + (5xy + 5y2 -5y)
= x(x + y - 1) + 5y(x + y - 1)
= (x + y - 1)(x + 5y)
x2+6xy+5y2-5y-x
=x2+6xy+9y2-4y2-5y-x
=(x+3y)2-(2y)2-5y-x
=(x+3y+2y).(x+3y-2y)-(5y+x)
=(5y+x).(x+y)-(5y+x)
=(5y+x).(x+y-1)